The choice and use of authentic documents to improve the linguistic level in a French as a foreign language class - Mahmoud, Victoria Mnati (Al-Adab Journal, 2020)
The use of authentic and well-chosen documents is an ideal support for the student, a reflection of a different culture. They are also excellent materials that allow, with a relevant pedagogical exploitation, to lead to a socialized final product outside the classroom. The fundamental purpose of using such documents is to make the students understand and interpret the information.